The Role of Innovation in the Performance of Maritime Services Using Unmanned Vessel Technologies - Rezaeian Asl, Hamid; Yadolahi farsi, Jahangir; Davari , Ali (Management Strategies and Engineering Sciences, 2024)
This study aims to investigate the role of innovation in improving the performance and competitiveness of small shipbuilding businesses and advanced maritime industry businesses in Hormozgan Province. The study employed a descriptive-survey research design, with data collected through structured questionnaires distributed to employees and experts in small shipbuilding businesses and advanced maritime industry businesses. The total sample size comprised 950 respondents. Statistical analyses, including one-sample T-tests and Pearson correlation tests, were performed using SPSS to evaluate the impact of various innovation indicators, such as entrepreneurial drivers, human capital, and technological advancements, on business performance and competitive advantage. The results showed that all innovation indicators had significantly higher mean scores than the neutral benchmark of 3 (p < 0.001), indicating their positive impact on performance. Key factors for small shipbuilding businesses included entrepreneurial drivers (mean = 4.43), human capital (mean = 4.95), and technological advancements (mean = 4.61). For advanced maritime industry businesses, human capital (mean = 4.88) and knowledge utilization (mean = 4.88) were critical contributors. Overall innovation performance scores were 4.14 for small shipbuilding businesses and 4.31 for advanced maritime industry businesses, highlighting the substantial role of innovation in both sectors. Innovation serves as a fundamental driver of performance and competitiveness in maritime businesses. Emphasizing human capital development, leveraging digital technologies, and fostering a culture of innovation are essential for sustainable growth. However, challenges such as limited collaboration and knowledge-sharing mechanisms need to be addressed to maximize innovation's potential impact.